Urban Transport Policies and the Environment: Evidence from Italy - Marco Percoco (Fondazione Eni Enrico Mattei (FEEM), 2007)
The paper reviews urban transport policies in Italian cities and their impact on the concentration of NO2 and PM10. Using parametric and non-parametric techniques, it finds no significant effect of the policy actions currently implemented. Further, it finds evidence of a weak positive impact of plans adoption. These results are interpreted as evidence of positive externalities among actions. Finally, by also discussing case studies, the paper points out the absence of economic instruments and argues that significant welfare gains would derive from their adoption.
Keywords: Q53; R41; 330; Urban Transport Policies; Traffic Externalities; Pollution Abatement; Stadtverkehrspolitik; Luftverunreinigung; Luftreinhaltung; Straßenverkehr; Italien